Migración, identidad y religión: aproximaciones al estudio del papel de la práctica religiosa en la redefinición identitaria de los migrantes mexicanos - Olga Odgers-Ortiz (Les Cahiers ALHIM)
Integration demands a redefinition of the identity of those that migrate as well as of those who stay. In this paper we argue that in the case of Mexican migrants to the United States religious practices play an important role in redefining their identity. Two main aspects are analyzed: the importance of religious practice in the socialization process of newcomers as well as the use of old traditional rites, such as celebrating Patron Saints, in the redefinition of ties with the home community.